A note on barriers to capital accumulation and income - John S. Landon-Lane; Peter E. Robertson (Rutgers University, Department of Economics, 2005)
In this paper we clarify the impact that barriers to capital accumulation can have on a two-sector neoclassical growth models ability to explain the observed differences in incomes across countries. We show that the effect of barriers to technology adoption in a two sector model is necessarily identical to a one-sector model when there are no factor market imperfections and each sector has identical technologies. We also show that this result generalizes to the case when the technologies are different across the sectors.
Keywords: F0; O0; O4; 330; Economic Growth; Economic Development; Barriers; Capital Accumulation